Integrating Clinical and Translational Research Networks-Building Team Medicine - Series 2 - Salgia, Ravi; Kulkarni, Prakash (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The previous Special Issue of the Journal of Clinical Medicine, 'Integrating Clinical and Translational Research Networks-Building Team Medicine', which highlighted our collective experience from the City of Hope and was published in 2020, was a huge success. Buoyed by the enthusiastic response from our peers and colleagues, we have embarked on bringing out Volume 2. The basic theme is the same-namely, integrating academic medical centers with the clinical network in various geographic locations to ensure that all patients, regardless of their physical proximity to major medical institutions, can benefit from recent clinical advances. As in the previous volume on the importance of including basic research scientists, our aim here is to highlight translational research approaches that leverage the combined knowledge, skills, experience, expertise, and vision of clinicians in academic medical centers, their affiliated community centers, and hospitals, together with those of basic research scientists. However, here we also strive to include bioinformaticians and data scientists. We look forward to sharing our team medicine experience with our colleagues around the world and trust that they will find the approach described in the articles included in this Special issue useful for guiding their approaches for treating cancer patients.